Eksplorasi Etnomatematika Pada K Eksplorasi Etnomatematika Pada Kelong Apung di Malang Rapat: Etnomatematika pada Kelong Apung - Harahap, Dwi Fajri Hasanah; Febrian, Febrian; Nurizati, Nurizati; Sanadia, Sanadia; Adelia, Marvina; Ambarita, Nova Indah; Candraningtyas, Rara; Rahmawati, Kurnia (Jurnal Gantang, 2023)
Mathematics taught in schools is often associated with the material needs of students; mathematics not only does not have to be understood in the school environment but also understood in other surrounding environments, such as culture and others. This study aimed to determine the ethnomathematics of Malay traditional floating kelong in Malang Rapat, Bintan Regency. The research method used is a descriptive qualitative method with an ethnomathematical approach. The research instruments used are observation sheets, interviews and documentation. Based on the research results presented, the author concluded, namely, the use of mathematical concepts in certain cultures and societies, such as the use of addition and subtraction in calculating the amount of wood used or the number of barrels used in floating kelongs. Making floating kelongs using basic mathematics, especially addition and subtraction operations, can be used to calculate the amount of wood used to construct floating kelongs and the number of barrels applied. Taxonomy is also applied to analyze and categorize certain elements in research, concerned with understanding how the components of floating kelong are classified or organized. The role of mathematics in identifying and calculating pesky components (materials that bring good luck or maintain security) used in floating kelongs. Ethnomathematics can also involve understanding the cultural themes underlying the use of mathematics in everyday life, such as how mathematical concepts are integrated with cultural beliefs and practices in the construction of floating kelongs.